Application of Behavioural Biometrics and Biomarkers for Calving Prediction in Bovines - Rasool, Akhter; Sakthivel, Jeyakumar; Thulasiraman, Sarath; Saroha, Harshit (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Timely and accurate prediction of parturition in bovine is crucial for optimizing maternal and fetal health, preventing dystocia and  minimizing periparturient complications. A multi-modal approach that integrates behavioural, physiological and molecular indicators  enables more precise calving prediction. Behavioural cues, such as increased frequency of lying and tail-raising in the final six hours  before parturition, combined with pelvic ligament relaxation triggered by elevated estrogen and relaxin, offer reliable external signs of  impending parturition. Key physiological markers include a significant drop in body temperature, vaginal temperature and ruminoreticular  temperature, alongside hormonal shifts particularly a decrease in progesterone and increases in prostaglandin F2α and estradiol  (E2), all of which are having significance in predicting parturition. Advanced monitoring systems and automated sensors capable of  tracking these parameters have proven valuable in improving periparturient cow management. Biomarkers, such as increased levels of  metalloproteinases, lactate dehydrogenase, α1-acid glycoprotein and haptoglobin, combined with a decrease in transthyretin, further  signal the onset of parturition. In addition, distinct metabolite profiles including changes in prostaglandins and lipid metabolites such  as glycerophospholipids, lysophosphatidylcholines, and sphingolipids, provide molecular insights into the proximity of parturition. This  comprehensive approach, combining behavioural, endocrine and biochemical markers, enhances the accuracy of parturition prediction,  ultimately improving reproductive success and reducing reproductive losses in cattle.
Keywords: Behaviour; Biomarker; Bovine; Hormones; Parturition; Prediction